Genre, territoire et promotion de la santé communautaire : enjeux théoriques et méthodologiques - Sara Aguirre Sánchez-Beato (Revue Francophone sur la Santé et les Territoires, 2015)
Health promotion is “the process of enabling people to increase control over, and to improve, their health” (OMS, 2009, p.1), putting the emphasis on the role of people as actors of their health. However, as Horrocks and Johnson (2014) claim, mainstream perspectives tend to conceptualize health-related actions as individually driven – hence the focus on lifestyles as a matter of choice. Drawing on these authors’ critical perspective, we consider these actions as social practices that are historically and geographically situated. In this article we address the relation between social categories – such as gender, class and ethnicity – and health-related social practices. In this regard, we propose intersectionality (Crenshaw, 1993) as an approach to study the interaction of social categories. In spite of the current interest that the intersectional approach has raised in the health field, its study has been mainly theoretical; therefore, more empirically-grounded research is needed. However, the empirical study of intersectionality is not unproblematic, its core principles raising a number of methodological challenges. In this article we present the theoretical and methodological proposal that conforms the core of our research about community health promotion in the Region of Brussels in order to address and empirically study the relation between gender, territory and health. Drawing on post-structural approaches the first part of the article presents a theoretical perspective to understand the complex relation between social categories, territory and health through the notion of health-related social practices. In this perspective the territory is considered in two different ways: as a methodological tool and –together with the body and individual ressources- as an element of health-related social practices. Community action being one of the main characteristics of health promotion programs (OMS, 2009), the definition and selection of a community is a key issue. In our research in the Region of Brussels a geographical approach towards community has been privileged, choosing the neighborhood – the space where daily life activities take place and to which inhabitants identify themselves (IBSA, 2007) – as the scale of analysis. This decision is motivated by several reasons. On the one hand, the key principles of intersectionality (Bowleg, 2012 ; Christensen et Qvotrup, 2012) – especially the mutual constitution of social categories and the idea that subjectivities are complex, intersecting and context-dependent – make the selection of categories for the intersectional analysis an “empirical open question” (Hancock, 2007, p. 251). Instead of selecting a particular group of the population based on a supposed common identity (i.e. ‘women’, ‘migrants’), we propose to analyze all the social categories that emerge from the whole population of a neighborhood (Christensen et Qvotrup, 2012). This strategy would prevent a ‘minoritising approach’ that risks the homogenization and stigmatization of certain groups (Giolla Easpaig et al., 2013). On the other hand health-related practices take place in particular contexts with symbolic and material dimensions. In our research the neighborhood is considered an element of these practices as it offers material resources and a differential access to them for different social categories present in this territory. A third set of reasons is the fact that participatory processes for community health promotion cannot be implemented in geographical spaces that are too big or too populous (Marchioni, 1999) and that behavioral change programs on a large scale often fail (Frohlich et Abel, 2014). Beyond an epidemiological perspective that focuses on the description and quantification of social inequalities of health, our research pays attention to the processes that lead to those inequalities. Instead of considering the individuals as being determined by the social systems, we suggest the adoption of a poststructural approach that conceives the relation between social categories and subjects as a bidirectional proccess (Staunaes, 2003) in order to overcome the traditional tension ‘structure-agency’. Drawing on Foucault’s notion of subjectification and Butler’s notion of performativity we define health-related practices as social practices that are influenced by the imbrication of social categories and at the same time contribute to their construction. That is, social categories are not what a subject is, but what a subject perform. We suggest an interactionist approach that takes into consideration not only the symbolic aspects of subjectivities but also the material ones. In particular we draw the attention to the role of the body, of individual ressources and of the ressources of the neighborhood as important elements of health-related practices. Together with this theoretical perspective we present a methodological proposal that attempts to overcome the methodological challenges raised by the intersectional approach that could inspire empirically grounded research in the health domain. In this regard, we suggest the group analysis method (Van Campenhoudt et al, 2009) as a useful tool to identify relevant health-related practices in the selected neighborhood(s). This technique allows the diversity of experiences of the participants to be considered and the most relevant social categories for the intersectional analysis to be identified. As in relation to the analysis of intersectionality itself, we propose the technique of the narratives as being able to capture the intersection of social categories as it is lived and experienced by the subjects (Christensen and Qvotrup Jensen, 2012). The topics of the narratives are based on the health-related practices identified in the previous phase. Finally, we propose a comparative approach – both within neighborhoods and inside neighborhoods – to better understand the processes that lead people to different health-related practices. To conclude, we draw attention to the potentialities that the incorporation of the intersectional approach to health promotion could offer, such as understanding health-related practices in all their complexity, understanding the link between social inequalities and health inequalities, the relation between the neighborhood, health and gender and the possible conception of programs that address the complexity of the population.